Technologies of the distributed generation: empirical evaluations of the innovations acceptance - A. V. Trachuk; N. V. Linder (Стратегические решения и риск-менеджмент)
The assessment of problems and prospects of application of technologies of the distributed generation is presented by the industrial companies. The concept of the distributed generation and structure of technologies included in it is considered, sources of key competitive advantages of use of technologies of the distributed generation are revealed. For the analysis of the most significant factors of perception of technologies of the distributed generationtheindustrialcompanieshaveconductedthedeepsemi-structuredinterviewstorepresentativesof 8 large industrial companies, questioning of representatives of 69 industrial companies. For the analysis the regression model, allowing to determine force and the importance of influence of the selected factors on acceptance by the companies of the decision on own generation is used.For the analysed companies possibility of technical connection, cost of the electric power and the apprehended advantages are critical factors of decision-making on use of technologies of the distributed generation. Risk factor has appeared we don’t mean. In deep interviews respondents explained it to that systems of the distributed generation minimize emergence of the listed adverse effects. Receiving cheap electric and thermal energy, gradual accumulation of power capacities, uniformity of capital investments with fast obtaining energy for production and economic needs is possible to day in connection with use of power effective decisions on the basis of technologies of the distributed generation.